2019
DOI: 10.1038/s41598-019-39250-x
|View full text |Cite|
|
Sign up to set email alerts
|

One-year postoperative skeletal stability of 3D planned bimaxillary osteotomies: maxilla-first versus mandible-first surgery

Abstract: Orthognathic surgery is carried out to correct jaw deformities and to improve facial aesthetics. However, controversy surrounds whether the maxilla- or mandible-first surgery approach leads to better surgical outcomes. In our previous study, we have shown that in most instances, the maxilla-first surgical approach yielded closer concordance with the 3D virtual treatment plan than a mandibular-first procedure. However, the post-operative stability of each approach has not been investigated. Therefore, this one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
0
14
1
2
Order By: Relevance
“…Skeletal stability after orthognathic surgery is controversially discussed in the literature and it was shown that postsurgical relapse mainly develops within the first 6 months after surgery [ 33 ]. Late relapse on the other hand tends to develop from 6 to 12 months after surgery and is believed to occur due to individual patient characteristics, such as condylar resorption as well as type, direction and magnitude of surgical displacements [ 34 , 35 ]. However, little is known about long-term stability after orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal stability after orthognathic surgery is controversially discussed in the literature and it was shown that postsurgical relapse mainly develops within the first 6 months after surgery [ 33 ]. Late relapse on the other hand tends to develop from 6 to 12 months after surgery and is believed to occur due to individual patient characteristics, such as condylar resorption as well as type, direction and magnitude of surgical displacements [ 34 , 35 ]. However, little is known about long-term stability after orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The OrthoGnathicAnalyser (OGA), as described in our previous study [ 11 ], was identified as the 3D assessment tool of choice, due to the application of VBM and the semi-automatic approach. Over time, the OGA has already been applied in large clinical studies [ 12 , 13 ], demonstrating its clinical applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies were planned using articulator models, and the relapse was measured by 2-dimensional lateral cephalometric tracing. Only Liebregts et al 6 have evaluated the overall 3-dimensional (3D) relapse for orthognathic surgery patients, but no study has specifically evaluated 3D relapse or skeletal stability in inferior maxillary repositioning. 7 The new 3D semi-automatic technique can be used to measure skeletal stability and relapse independent of postoperative orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%